The peculiarities to form vegetable marrow yield depending on climatic conditions - Пузік, Л. М.; Образцова, З. Г. (Scientific Progress & Innovations, 2012)
Based on years of research studied the effect of the sum of effective air temperature and rainfall during the growing season on yield and zucchini on the basis of statistical data processing methods disperse, correlation and regression analysis using Statistica package Exsel and found that the variability of the yield was low (5.39% ), but inferior to the sum of temperatures (7.38%) and rainfall (16.63%). Statistical parameters of meteorological factors and yields indicate that between yield and total precipitation and the sum of effective temperatures there is little feedback.